A influência dos métodos científicos na Geografia Física - Rodrigues Nunes, João Osvaldo; SANT´ANNA NETO, João Lima; Garcia Tommaselli, José Tadeu; Trindade Amorim, Margarete Cristiane de Costa; Perusi, Maria Cristina (Terra Livre, 2015)
nt